Active damping of driveline vibration in power-split hybrid vehicles based on model reference control. (October 2019) - Liu, Hui; Zhang, Xun; Chen, Yinqi; Taha, Mahmoud; Xu, Haoxin
Abstract: The power-split hybrid vehicles are widely used owing to its advantages of high efficiency and low emission. With the increasing of the requirements of the customer's satisfaction nowadays, vibration control is getting progressively more attention. Since the transmission system components are elastic to some extent, meantime the torque of the motor responds quickly for a sudden acceleration, hence torsional vibration takes place, henceforth the passengers will suffer inconvenience attributable to this vibration. This paper studies the active control algorithm for the torsional vibration of the power-split hybrid powertrains under rapid acceleration and deceleration circumstances. Primarily, a dynamic modeling of the power-split hybrid vehicle is built, in addition the uncertainty caused by the variable transmission ratio is analyzed. Moreover, this paper proposes a method combining the model reference adaptive control and the pole configuration method to solve the torsional vibration active control problem with uncertainties. The reference model is constructed by pole configuration method. Based on the dynamic characteristics of the reference model, the model reference adaptive control is implemented and the torque ripple reduction of output shaft under the impact conditions is achieved. Furthermore, this paper designs a dynamic coordinated control algorithm combined with active vibration control strategy, which ensures the dynamic performance and comfort performance of the vehicle. Finally, the effectiveness of this active vibration control strategy under cyclic conditions is verified using Simulink simulation and hardware-in-loop simulation. Highlights: A dynamic model of hybrid vehicles that shows the uncertainty of system is proposed. An active vibration control algorithm is proposed to active damping the vibration. A dynamic coordinated control strategy is proposed to ensure the dynamic performance.